Peran Guru PAI dalam Menguatkan Moderasi Beragama di Sekolah - Rian Hidayat (TA'DIB: Jurnal Pendidikan Agama Islam, 2025)
Religious moderation is a concept that emphasizes a tolerant, fair, and balanced attitude in religious life, so that it is an important factor in maintaining social harmony in the school environment. Islamic Religious Education (PAI) teachers have a strategic role in strengthening religious moderation through the learning process, example, and social interaction with students. This study aims to analyze the role of PAI teachers in strengthening religious moderation in schools and the strategies applied in building inclusive and tolerant attitudes among students. The method used in this study is a qualitative approach with data collection techniques in the form of interviews, observations, and documentation studies. The results of the study show that PAI teachers play a role as facilitators, motivators, and models in forming moderate religious understanding. The implementation of religious moderation values is carried out through integration in the curriculum, dialogical approach in learning, and extracurricular activities based on inclusivity. This research recommends strengthening teachers' capacity in teaching religious moderation as well as synergy with schools and the community in creating a harmonious and tolerant educational environment.